Kajian Perilaku Konsumen Era Pandemi: Pendekatan Turbulent Marketing - I Made Suardana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research attempts to study the application of turbulent marketing in the pandemic era, by paying attention to consumer behavior. The type of research used is literature research, because it focuses more on theoretical studies and supports relevant empirical research. The results of the study show that turbulent marketing in the pandemic era (turbulent environment-chaotics) is not carried out immediately, but only for companies that have unique values and have made change their corporate climate. The company builds the value of excellence through value chain implementation, the application of smart cooperation with employees, ethics from principals and agencies and has been able to get value from the community (potential and effective consumers). Companies can generate consumer interest and emotion from promotions, but still provide more value to consumers at the expense of consumers and competitors. Building effective communication with consumers, even to the point of getting the company's product creations, implements co-creation